1998
DOI: 10.1046/j.1365-2885.1998.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of furosemide in horse racing: its effects and regulation

Abstract: Furosemide has been used empirically and has been legally approved for many years by the US racing industry for the control of exercise-induced pulmonary haemorrhage (EIPH) or bleeding. Its use in horses for this purpose is highly controversial and has been criticized by organizations outside and inside of the racing industry. This review concentrates on its renal and extra-renal actions and the possible relationship of these actions to the modification of EIPH and changes in performance of horses. The existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Prerace administration of frusemide is regarded as the most effective way to reduce the severity of EIPH; and i.v. injection has been associated with a significant improvement in racing times of Thoroughbreds and Standardbreds (Soma and Uboh 1998;Geor et al 2001). It has been presumed, but not demonstrated, that this improvement is linked to a reduction in the severity of EIPH.…”
Section: Introductionmentioning
confidence: 99%
“…Prerace administration of frusemide is regarded as the most effective way to reduce the severity of EIPH; and i.v. injection has been associated with a significant improvement in racing times of Thoroughbreds and Standardbreds (Soma and Uboh 1998;Geor et al 2001). It has been presumed, but not demonstrated, that this improvement is linked to a reduction in the severity of EIPH.…”
Section: Introductionmentioning
confidence: 99%
“…5 The most common use of furosemide in the horse, however, is to attempt to decrease severity of exercise-induced pulmonary hemorrhage in racing horses, although the rationale and effects of furosemide in this context are highly debated. 6,7 Furosemide is routinely administered by injection IV or IM (250-500 mg q6-8h). 8 Furosemide is effective after administration PO in other species, and administration PO is often suggested as an alternative to parenteral administration in long-term treatment of horses with congestive heart failure 2,9,10 ; however, documentation of its pharmacokinetic or pharmacodynamic characteristics after administration PO has not been reported.…”
mentioning
confidence: 99%
“…However, a recent investigation showed that furosemide was able to decrease the incidence and severity of EIPH in thoroughbreds (Hinchcliff et al 2009). It should be stressed that epidemiological surveys have provided evidence that furosemide may improve racing performance (Soma and Uboh 1998). In horses, furosemide decreased the oxygen debt and the rate of blood lactate accumulation.…”
Section: Doping Agents and Doping Control Issuesmentioning
confidence: 99%
“…In horses, furosemide decreased the oxygen debt and the rate of blood lactate accumulation. This effect can be reversed by adding to the horse a weight compensating for the loss of body weight due to the diuresis produced by furosemide (approximately 16 kg), suggesting that changes in performance observed in bleeder horses after a furosemide treatment is due to a small reduction in body weight and not to a selective pharmacological action on bleeding mechanisms (Soma and Uboh 1998;Zawadzkas et al 2006). In addition, furosemide is disapproved of because it causes diluted urine, i.e.…”
Section: Doping Agents and Doping Control Issuesmentioning
confidence: 99%